STUDY ON LOCUS OF CONTROL CONTRIBUTING TO SUPERSTITIOUS BEHAVIOR - Shrivastav, Manasvi (International Journal of Research -GRANTHAALAYAH, 2018)
The purpose of the study is to assess the relationship between locus of control and superstitious behavior of people of UP. 300 participants were selected through quota sampling from various places of UP. Age and education related factors treated as controlled variables. To assess locus of control in subjects Hindi adaptation of “Rotter’s Locus of Control scale” of Dr. Anand Kumar & S.N. Srivastav has been used. It consists of 29 items in it. Superstitious Behavior Scale (self-constructed) has been used, which is consisting of 40 items. Each item have three alternatives: (a) I will definitely do it. (b) If not possible, I will not do it. (c) I don’t believe in it. Ex-post facto research design has been used. Data is analyse by chi-square method. Result show that external locus of control is responsible for high superstitious behavior.